Urban-originated English language teachers longevity: what keeps them in rural schools in Sabah? / Ameiruel Azwan Ab Aziz … [et al.] - Ab Aziz, Ameiruel Azwan; Jamil Azhar, Sheik Badrul Hisham; Mabsah, Nurul Nadya; Mikeng, Damien (Universiti Teknologi MARA, 2021)
The shortage of trained and qualified English language teachers in rural schools has always been a significant issue in Malaysia, particularly in Sabah, due to the higher proportion of rural areas. Various factors have been associated with teachers’ reluctance to serve in rural schools. Nevertheless, several urban-originated teachers are recorded to have shown persistence in serving rural schools. The purpose of this paper is to investigate the reasons and contributing factors behind their long-term longevity in rural schools. The lived experiences of ten teachers were explored through in-depth semi-structured interviews. Data gleaned were thematically analysed following Ryan and Bernard’s (2000) recommended procedures. Results suggest that even participating teachers work in a challenging English teaching environment; this has not been a sufficient drive for them to depart from rural schools. Their longevity is attributed to perceived social support and students factor. Furthermore, a blended concept of positive emotions was remarked as a fuel-source of teachers’ long-term persistence in rural schools. The contributions and implications of the study are also discussed.